Description of Islamic Patterns in the Archipelago in the subjects of PAI in Elementary Schools - Nur laila (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Religion and culture of the elementary schools are two different things but very closely related the majority of people are very complicated or quite difficult to distinguish the absolute religion and which culture becomes an expression well as vehicle and relatively it. Of course the inability of a person to distinguish lack of clarity is causing chaos in thinking epistemological side, chaos in the sense of hierarchy where the value associated with the higher values and the lower values which is absolute and which are relatively of the elementary schools. Departing of the elementary schools from these problems .using the historical anthological approaches and methods of analysis –critical then this article tries to discuss about archipelagic Islam. The main stress ion is in the epistemological analysis of archipelagic Islam. The main critical analysis carried out toward archipelagic Islam is expected to map which aims unveil what should be retained and that what should be deconstructed the conclusion from this study is the dialectic between religion that have moral and universal values with the culture and traditions of the people of Indonesia to from a distinctive style of Indonesian Islam is commonly called archipelagic Islam especially the elementary schools.